2017
DOI: 10.5539/ass.v13n11p157
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Lifestyle on Online Purchasing Decision for Electronic Services: The Jordanian Flying E-Tickets Case

Abstract: This study aims to examine how Jordanian passenger's lifestyle effects their buying decisions of online e-tickets by utilizing the AIO theory (Activities, Interests, and Opinions). A convenience sample of 473 passengers from the Jordanian airport was chosen as the population in order to verify the hypotheses and research framework. The results of the study show that the lifestyle of Jordanian passengers significantly influences their purchase of e-tickets. The analysis of the results indicates that each of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 35 publications
2
8
0
2
Order By: Relevance
“…Therefore, based on the study statistical results, the study found that there is a positive relationship between information technology (electronic data interchange and enterprise resource planning) and organizational performance in the pharmaceutical companies in Jordan. These results are consistent with (Chandler, 1998;Sanchez-Rodriguez and Martinez-Lorente, 2011;Rodríguez-Escobar and González-Benito, 2015;Mandal, 2015;Aldmour et al, 2017), the findings of this research endorse the idea that information technology is seen as empowerment tool to support and promote organizational performance for the firm's and financial outcomes. Additionally, the successful implementation of information technology in the pharmaceutical companies will improve and enhance the quality of company procedures; (such as, work efficiency, productivity and effectiveness).…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, based on the study statistical results, the study found that there is a positive relationship between information technology (electronic data interchange and enterprise resource planning) and organizational performance in the pharmaceutical companies in Jordan. These results are consistent with (Chandler, 1998;Sanchez-Rodriguez and Martinez-Lorente, 2011;Rodríguez-Escobar and González-Benito, 2015;Mandal, 2015;Aldmour et al, 2017), the findings of this research endorse the idea that information technology is seen as empowerment tool to support and promote organizational performance for the firm's and financial outcomes. Additionally, the successful implementation of information technology in the pharmaceutical companies will improve and enhance the quality of company procedures; (such as, work efficiency, productivity and effectiveness).…”
Section: Discussionsupporting
confidence: 91%
“…Iy means that younger participants are more likely to possess higher subjective norms and higher intentions to buy e-ticket cinema. Aldamour et al (2017) stated that younger consumers tended to use the latest technology and applications when ordering or buying flight tickets, while older consumers tended to use the traditional way. Also, it is essential to understand the age of consumers because each individual of a different age will use different products and services (Sumarwan, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Improvement in quality procedures lead to increased profitability and increased sales (Flanigan, 2012). Leadership Leadership is cited as the most dominant and acknowledged dimensions of TQM strategy (Hitt and Ireland, 2002;Aldmour et al, 2017). According to Hitt and Ireland (2002), the success of an organization is largely determined by the ability of leaders to utilize both human and social capital to create a competitive advantage.…”
Section: Enhancement Of the Quality Proceduresmentioning
confidence: 99%